Exploring Visual Analytic Tools for Antimicrobial Stewardship Intervention across 8 Veterans Affairs Hospitals. (4th October 2017) - Sutton, Jesse; Graber, Christopher J; Madaras-Kelly, Karl; Jones, Makoto; Glassman, Peter; Spivak, Emily; Goetz, Matthew
Abstract: Background: Antimicrobial use (AU) measurement is a core element of antimicrobial stewardship (AS). Although National Healthcare Safety Network (NHSN) AU option and Standardized Antimicrobial Administration Ratios (SAAR) facilitate automated data collection and benchmarking, they are limited by inability to connect AU to indications or timing within a treatment course. Methods: We developed tools that analyze SAAR AU group data for pneumonia (PNA), urinary tract infection (UTI), and skin and soft-tissue infection (SSTI) at decision points within a treatment course: Choice (days 0–2), Change (3–4), and Completion (5–6) (CCC). The tool is being tested by AS teams at 8 VA hospitals. We report AU for PNA, UTI, and SSTI during 2016 in non-ICU patients to illustrate between facility variation within SAAR groups and patterns of change across CCC. Results: There was substantial inter-site variation in the use of the SAAR groups across CCC for patients with PNA, UTI or SSTI (Figure). For all sites, the use of antibiotics with activity against MRSA or multi-drug resistant GNR (MDRO) decreased from Choice to Change and Completion. In contrast for Broad-Spectrum antibiotics used for Community-Acquired (CA) infections, use decreased over time for Sites, A, B, D, E and F, but not at sites C, G and H. The only SAAR group to show ≥5% increased use over CCC across all infections was Surgical Site Infection Prophylaxis (SSIP) antibiotics (sites F, G and H). Assessment by indication showed ≥5% increases for CA (PNA, site F; SSTI, sites B, C, D, E and G), SSIP (PNA, site F; UTI, sites F and H; SSTI, sites D, G and H), and MRSA (UTI, sites C and E); use of MDRO antibiotics consistently decreased. Conclusion: Our tool provides an automated method to analyze syndrome-specific AU at key decision points, which allowed AS teams to efficiently and reproducibly identify areas for intervention. The most notable inter-hospital variation was among the pattern of use CA and SSIP agents across CCC especially for SSTI as de-escalation to CA occurred at 5 sites and to SSIP at 3 sites. De-escalation to SSIP for PNA also occurred at one site. The contribution of treatment vs. prophylaxis indications for SSIP SAAR AU warrants further investigation given implications for AS intervention. Disclosures: All authors: No reported disclosures.